Image recoloring for people with protanomaly and deuteranomaly of various severity - V. V. Sinitsyna (Системный анализ и прикладная информатика)
As part of the conducted research, a method was developed to help people with the most common forms of anomalous trichromacy deuteranomaly and protanomaly and any severity of these anomalies in visual perception of information. For protanomalies, colors with a predominant red component are transformed, and for deuteranomalieswith a predominant green component. Recoloring for both forms of the anomaly is performed in the CIE L*a*b* color space using the conversion coefficients obtained using the simulation method of Machado et al. Among the advantages of this method, it is worth noting the ability for each user to customize such personalized recoloring parameters as the coefficient of changing the recoloring component and the coefficient of changing the brightness of images in accordance with their individual perception of visual information. In addition, as a result of the method, each color changes equally in all areas of the image.The correctness of the method operation was verified by examining a simulated image for deuteranomalous and protanomalous vision with a normal trichromat, as a result of which the image areas previously inaccessible to the vision of the anomalous trichromat became distinguishable. The quality of recolor-ing was also assessed by the loss of color naturalness, which for the test images had satisfactory values and varied within the range from 1.37 to 10.9 depending on the severity of the anomaly. The execution time of the method for both cases of anomalous trichromacy indicates a high speed of image processing and is 0.08 s for images of 750 000 pixels.